2013
DOI: 10.1371/journal.pbio.1001494
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Acts with the Temporal Cascade to Promote Neuroblast Cell Cycle Exit

Abstract: During the development of the Drosophila nervous system, the developmentally regulated Hedgehog pathway, together with a series of temporal transcription factors, schedules the end of neurogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 93 publications
(103 reference statements)
5
67
2
Order By: Relevance
“…Biochemical studies have not only shown that PTPA reactivates the serine/threonine phosphatase activity of inactive PP2A, but also that it increases peptidylprolyl cis-trans isomerase activity (Chao et al, 2006). Consistently, the yeast PTPA homologs Ypa1 and Ypa2 can physically bind to the yeast PP2A homologs Pph21 and Pph22.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Biochemical studies have not only shown that PTPA reactivates the serine/threonine phosphatase activity of inactive PP2A, but also that it increases peptidylprolyl cis-trans isomerase activity (Chao et al, 2006). Consistently, the yeast PTPA homologs Ypa1 and Ypa2 can physically bind to the yeast PP2A homologs Pph21 and Pph22.…”
Section: Introductionmentioning
confidence: 90%
“…The following fly stocks were used in this study: wor-gal4, Df(2L)BSC163, Df(2L)BSC164, Df(2R)BSC359, mts XE-2258 (Betschinger et al, 2003), UAS-mira::3GFP (gift from C. Petritsch, UCSF). MACRM clones were generated as previously described (Chai et al, 2013). For GFP-labeled Ptpa 1 mutant clones, we used an elav-gal4,hs-FLP;UAS-nlacZ,UAS-mCD8::GFP;P[FRT]40A, Fig.…”
Section: Fly Strainsmentioning
confidence: 99%
“…Ecdysone acts together with the Mediator complex and Syncrip to promote neuroblast size reduction, nuclear Prospero localization, and terminal differentiation [36, 58]. This late event also requires Hedgehog signaling [59], and down-regulation of Imp [60]. The detailed mechanism of ecdysone, Mediator, and Hedgehog signaling remains to be determined.…”
Section: Hormonal Cues Regulate Larval Neuroblast Temporal Identitymentioning
confidence: 99%
“…As with abdominal VNC NBs, embryonic Cas induces Grh expression, and after hatching, Cas induces Hh expression in these NBs (Chai et al . ). Hh signaling acts as an autocrine and/or paracrine factor to sustain Grh expression, which in turn prevents premature nuclear localization of Pros to exit the cell cycle (Maurange et al .…”
Section: Termination Of Nb Proliferationmentioning
confidence: 97%
“…Type I and Type II NBs in the central brain and thoracic VNC NBs use similar termination machinery, where they begin to shrink following puparium formation, and most NBs exit the cell cycle at approximately 24 h after puparium formation (APF) (Figs 1C, 7B) (Ito & Hotta 1992;Maurange et al 2008;Homem et al 2014). As with abdominal VNC NBs, embryonic Cas induces Grh expression, and after hatching, Cas induces Hh expression in these NBs (Chai et al 2013). Hh signaling acts as an autocrine and/or paracrine factor to sustain Grh expression, which in turn prevents premature nuclear localization of Pros to exit ª 2015 Japanese Society of Developmental Biologists the cell cycle (Maurange et al 2008).…”
Section: Termination Of Nb Proliferationmentioning
confidence: 99%